If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -2 = -23 + 9z Reorder the terms: -2 + 2z = -23 + 9z Solving -2 + 2z = -23 + 9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-9z' to each side of the equation. -2 + 2z + -9z = -23 + 9z + -9z Combine like terms: 2z + -9z = -7z -2 + -7z = -23 + 9z + -9z Combine like terms: 9z + -9z = 0 -2 + -7z = -23 + 0 -2 + -7z = -23 Add '2' to each side of the equation. -2 + 2 + -7z = -23 + 2 Combine like terms: -2 + 2 = 0 0 + -7z = -23 + 2 -7z = -23 + 2 Combine like terms: -23 + 2 = -21 -7z = -21 Divide each side by '-7'. z = 3 Simplifying z = 3
| -4.9x^2+17x-8=0 | | -2=-1+k/4 | | -8-7=6x+2-5x | | 8+3x^2+2(8+3x)-3=0 | | 4p+12-3q-4q-18+6q= | | 5(x+6)=(x+7) | | (2x-3y)=(x+3y) | | -0.05x-0.05=0.5 | | 2(b+1)-(3+b)=-2 | | 125/0.38 | | 4x+x-3=4x+5 | | 0.38/125 | | 2x+15=3x-45 | | 6(3+2x)-5=25 | | 2-t=5+2t | | 17x^2-24xy=0 | | -1+3x=2x+11 | | 7-16-(-3-4)= | | -17+10-61-(-3)= | | 2(x+1)=2(x+3) | | (4x-1)^1/2=6 | | -16+10-61-(-3)= | | (5y+7)-(4+4y)=9 | | 3n^2-20n=-32 | | 10-5b=110 | | 2/3r=6 | | 8x+44=12x | | q/4+7=5 | | 2.4+(-3.7)= | | -3.8-2.9= | | -9-9-9-9= | | -60-(-8-3)= |